2015
DOI: 10.1371/journal.pone.0136282
|View full text |Cite
|
Sign up to set email alerts
|

Association of IL10 Polymorphisms and Leprosy: A Meta-Analysis

Abstract: Leprosy is a chronic infectious disease that depends on the interplay of several factors. Single nucleotide polymorphisms (SNPs) in host immune related genes have been consistently suggested as participants in susceptibility towards disease. Interleukin-10 (IL-10) is a crucial immunomodulatory cytokine in mycobacterial pathogenesis and especially the -819C>T SNP (rs1800871) has been tested in several case-control studies indicating association with leprosy risk, although a recent consensus estimate is still mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
1
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 31 publications
0
29
1
6
Order By: Relevance
“…Many studies have reported an association between the IL-10 gene polymorphism and the development of inflammation-related diseases such systemic lupus erythematosus, coronary artery disease, peptic ulcer disease, Behçet's disease, lupus nephritis, and leprosy (Cheng et al, 2010;da Silva et al, 2014;Al-Okaily et al, 2015;Alvarado-Arnez et al, 2015;Krasnova et al, 2015;Yang et al, 2015). Cheng et al (2010) reported that IL-10 -819T/C and -592A/C genetic polymorphisms are associated with an increased risk of erosive reflux esophagitis and gastritis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies have reported an association between the IL-10 gene polymorphism and the development of inflammation-related diseases such systemic lupus erythematosus, coronary artery disease, peptic ulcer disease, Behçet's disease, lupus nephritis, and leprosy (Cheng et al, 2010;da Silva et al, 2014;Al-Okaily et al, 2015;Alvarado-Arnez et al, 2015;Krasnova et al, 2015;Yang et al, 2015). Cheng et al (2010) reported that IL-10 -819T/C and -592A/C genetic polymorphisms are associated with an increased risk of erosive reflux esophagitis and gastritis.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Okaily et al (2015) carried out a study with 272 Saudi subjects, and suggest that IL-10 -1082A/G, -819T/C, and -592A/C genetic variations are associated with the risk of Behçet's disease. Alvarado-Arnez et al (2015) conducted a meta-analysis study, and have reported that IL-10 -819T/C is associated with leprosy susceptibility. Krasnova et al (2015) have suggested that the IL-10 gene polymorphism is associated with the severe course of the disease.…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 is a pleiotropic cytokine, and a wealth of evidence supports its regulatory role in the pathology process of several kinds of diseases (Alvarado-Arnez et al, 2015;Ghaleh Baghi et al, 2015;Hsu et al, 2015;Khodaeian et al, 2015). In addition, experimental studies indicated that IL-10 expression could maintain the balance between proinflammatory and anti-inflammatory stimuli in the process of cerebrovascular disease.…”
Section: Discussionmentioning
confidence: 99%
“…The gene encoding IL-10 (IL10) is present on the chromosomal locus 1q31-32, and several genome regions of chromosome 1 (1q21-23, 1q31-32 and 1q42-44) have been observed to be correlated with development of several kinds of diseases, such as diabetes mellitus, peptic ulcer disease, coronary artery disease, leprosy, chronic hepatitis B infection, and oral cancer (Alvarado-Arnez et al, 2015;Ghaleh Baghi et al, 2015;Hsu et al, 2015;Khodaeian et al, 2015;Miftahussurur and Yamaoka, 2015;Yang et al, 2015). The authors of previous researches have reported the correlation of IL10 gene polymorphisms with the ischemic stroke risk; however, the results are inconsistent (Munshi et al, 2010;Sultana et al, 2011;Xie et al, 2013;Qi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The production of the IgG, IgA, and IgM isotypes induced by IL-4 is synergistic with IL-10 [38]. However, high levels can contribute to the maintenance of the parasite in the host and can be related to cerebral malaria and high levels of parasitemia [20, 21, 24].…”
Section: Introductionmentioning
confidence: 99%